Impact of mutations at Arg220 and Thr237 in PER-2 β-Lactamase on conformation, activity, and susceptibility to inhibitors - Ruggiero, Melina (2017)
PER-2 accounts for up to 10% of oxyimino-cephalosporin resistance in Klebsiella pneumoniae and Escherichia coli in Argentina and hydrolyzes both cefotaxime and ceftazidime with high catalytic efficiencies (kcat/Km). Through crystallographic analyses, we recently proposed the existence of a hydrogen bond network connecting Ser70-Gln69-oxyanion water-Thr237-Arg220 that might be important for the activity and inhibition of the enzyme. Mutations at Arg244 in most class A β -lactamases (such as TEM and SHV) reduce susceptibility to mechanism-based inactivators, and Arg220 in PER β -lactamases is equivalent to Arg244. Alterations in the hydrogen bond network of the active site in PER-2, through modifications in key residues such as Arg220 and (to a much lesser extent) Thr237, dramatically impact the overall susceptibility to inactivation, with up to 300-And 500-fold reductions in the rate constant of inactivation (kinact)/Kivalues for clavulanic acid and tazobactam, respectively. Hydrolysis on cephalosporins and aztreonam was also affected, although to different extents compared to with wild-Type PER-2; for cefepime, only an Arg220Gly mutation resulted in a strong reduction in the catalytic efficiency. Mutations at Arg220 entail modifications in the catalytic activity of PER-2 and probably local perturbations in the protein, but not global conformational changes. Therefore, the apparent structural stability of the mutants suggests that these enzymes could be possibly selected in vivo.